Pengetahuan Kesaguan Guyub Tutur Biak Numfor â Papua: Studi Awal Linguistik Kebudayaan - Warami, Hugo (Universitas Papua, 2017)
This article aims to reveal the cognitive system of the language in the speech community of Biak Numfor - Papua the sago knowledge about the form that has traditionally been inherited for a long time. Biak Numfor Speech community here inafter abbreviated GTBN. The sago knowledge and a wealth of cultural resources possessed mental GTBN. One form of the sago knowledge which will be described in this presentation is sago as a food system, namely (i) human existence with all its attributes can be identified through and by means of cooking food, (ii) to cook and eat a meal marking the transition from nature (natural) to culture. This knowledge is a means that is universal in nature transform knowledge into cultural knowledge. This article will be revealed through the paradigm of cultural linguistics with the structural analysis model Levi-Strauss. This article will focus on efforts to explorations of the sago knowledge disclosure issues that include: (i) sago langue as a system and (ii) sago as the parole system.Â